Spodziewane skutki członkostwa Polski w Unii Europejskiej dla małych i średnich przedsiębiorstw - Jarenko, Mariusz A. (My University, 2001)
W związku z oficjalnym rozpoczęciem negocjacji Polski z Unią Europejską, co nastąpiło 31 marca 1998 roku, przystąpienie naszego kraju staje się coraz bardziej realne. Bowiem nowe otoczenie rynkowe wymagać będzie od polskich firm zastosowania procesów dostosowawczych do nowych warunków rynkowych. Przedsiębiorstwa będą zmuszone dokonać wielu zmian w obrębie stosowanej dotychczas orientacji rynkowej. Od polskich firm działających na bardzo konkurencyjnym obszarze eurorynku wymagane jest już dzisiaj zastosowanie nowoczesnych form zarządzania oraz europejskiej orientacji rynkowej. Przedsiębiorstwa, które wcześnie przeprowadzą konieczne procesy dostosowawcze, będą odnosić korzyści z wykorzystania możliwości, jakie stwarza Europejski Rynek Wewnętrzny ( ERW). Motywem podjęcia tematu pracy jest integracja Polski z Unią Europejską oraz związana z tym niepewna sytuacja polskich przedsiębiorstw. Celem natomiast jest ukazanie skutków integracji dla małych i średnich przedsiębiorstw.

The primary goal of the adjustment processes of Poland’s economy to the requirements of the UE, which have continued for many years, is increasing its competitivens on the European market. International economic integration is one of the most important occurrences second halves of XX age. Integration Poland with European Union is the most important strategic of target for our country. In relationship with official beginning of negotiation Poland with European Union, March 1998, accession of our country becomes more and more real. The analysis of international competitivens of Poland on the European Union markets shows that Poland ranks very low as regards economic potential and trade with this organization. The topic of the thesis is „The results of Poland membership in European Union for MSP (little and average organizations)”. The motive of this work is integration Poland with and connected from this insecure situation Polish organizations. First chapter shows European Integration, embracing her genesis, notion and organs with their competences. The chapter includes also the polish preparatory process to memberships. The second chapter remained challenges which stand before MSP in circumstances of European Integration. The chapter describes the notion MSP, the circumstances of working, and governments policy of states UE in the face section MSP. The last chapter focuses on methodological problems of the work. It contains principal and range of the work, investigative hypothesises. One introduced here also the polish section of MSP in perspective of membership, barriers of development and results of integration for this kind of organization. Besides one presented the short case study on example " WENTA" organization as polish firm in circumstances of integration with European Union.
Keywords: Unia Europejska; integracja z UE; MŚP w UE; system podatkowy; Przedsiębiorstwo Wielobranżowe „WENTA”